2022
DOI: 10.1109/access.2022.3217480
|View full text |Cite
|
Sign up to set email alerts
|

Software Defect Density Prediction Using Deep Learning

Abstract: Delivering a reliable and high-quality software system to client is a big challenge in software development and evolution process. One of the software measures that confirm the quality of the system is the defect density. Practitioners usually need this measure during software development process or during a period of operation to indicate the reliability of software system. However, since predicting defect density before testing the modules is time consuming, managers need to build a prediction model that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, data sparsity involved in defect density prediction was not made. To address on this issue, deep learning was applied in [17] to handle data sparsity in defect density. Yet another graph-based ML was presented in [18] by taking into consideration CNN for ensuring accuracy involved in prediction.…”
Section: Related Workmentioning
confidence: 99%
“…However, data sparsity involved in defect density prediction was not made. To address on this issue, deep learning was applied in [17] to handle data sparsity in defect density. Yet another graph-based ML was presented in [18] by taking into consideration CNN for ensuring accuracy involved in prediction.…”
Section: Related Workmentioning
confidence: 99%
“…A normality test on the four metrics showed that the number of developers and code churn significantly affected defect density. Recently, Alghanim et al 38 proposed a deep learning model based on GRNN to predict the defect density.…”
Section: Related Workmentioning
confidence: 99%
“…However, various studies have indicated that DL techniques, which excel in learning semantic features, outperform ML techniques in software defect prediction (SDP) (Tong et al, 2018) Moreover, ML techniques rely on manual feature selection (Young et al, 2018). As a result, there has been a growing interest in exploring the application of autoencoders, a speci c type of neural network architecture, for software defect prediction in recent years (Eivazpour and Keyvanpour, 2019;Qasem et al, 2020;Alghanim et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%
“…Overview of SDP studies based on machine learning and deeplearning techniques : This research proposes a defect prediction model based on deep learning with an attention mechanism. The study introduces an attention-based long short-term memory (LSTM) network to capture important features and patterns from software metrics Alghanim et al, 2022;…”
mentioning
confidence: 99%